Ku nieśmiertelnej sławie – Tomasz Zamoyski w oracjach pogrzebowych - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Tomasz Zamoyski died on the 8th of January 1638 (born on the 1st of April 1594). The text is a presentation and analysis of four, conceptual and funeral orations, which were written by: Stanisław Szałapski SJ, Bartłomiej Sylwiusz SJ, Marek Korona and Mikołaj Ławrynowicz. The first part of the article is a presentation of conceptual structure of orations and as well as analysis of titles and role of mottos from Bible. The second part of article describes Tomasz Zamoyski’s glowing effigy. Author uses rhetorical scheme laudatio personae, which was constructed from circumstances inner (family stock, ancestors, birth, education, attributes of body and soul, actions) and external (family, friends, descendants, time of his life, types of death). Orators built the glowing effigy of Tomasz Zamoyski, and his life presents a humanistic model of human and citizen.